Esensi Penguatan Etika Politik Islam di Indonesia - Nisya, Khoirun; Nasrung, Nur Aulia; K, Kurniati (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The essence of strengthening Islamic political ethics in Indonesia which underlines the need for harmony between religious principles and political governance. This requires integrity, transparency and justice as the basis for leaders and society in carrying out politics based on Islamic values. The theoretical aim of this research is to provide an academic contribution related to moral guidance for political leaders and the general public which will later provide an understanding regarding the essence and strengthening of ethics by integrating Islamic values into political practice in Indonesia which can form better political policies. a political system that is fair, transparent and socially just. The leadership system generally does not explain the role of politics and community participation, this is what encourages researchers to examine the essence and strengthening of Islamic political ethics. The research method used is a qualitative-interpretive method by conducting a literature study from one source. Then the data obtained will be collected, studied and synthesized and then analyzed carefully to get answers to the problems posed.